(untitled) (Quinto Sol, 2011)
The gradual provincialization process of national territories not only reveals forward and backward steps in its materialization; it also allows a reflection about substantial aspects of Peronism: its political conception, legislative practices and its flexible doctrine. This article investigates the parliamentary debates about the alternatives of incorporation of National territories’ inhabitants into the political body of the Nation by examining the changing arguments related to the representation of the Republic and the assessment of the executive and legislative powers within the “Nueva Argentina”.